Development Of A Folded Dipole Antenna for IoT Networks - Sha'ari, Mia Shazrena; A Majid, Huda; Najib Mohammed Ahmed Al-Fadhali (Progress in Engineering Application and Technology, 2025)
The development of optimized antenna designs is necessitated by the increasing demand for efficient and cost-effective communication solutions in IoT networks. In this study, a folded dipole antenna tailored for IoT applications is designed, with precise simulation and analysis conducted using CST Studio Suite software. The folded dipole antenna offers numerous advantages, including enhanced impedance matching, wide bandwidth, and compact size, making it a suitable candidate for IoT devices that require reliable and low-power communication. A systematic design approach was employed, incorporating both theoretical analysis and simulation tools within CST Studio Suite to optimize the antenna’s performance. The design parameters were meticulously adjusted to achieve the desired frequency response, impedance matching, and radiation pattern, ensuring compatibility with the operational frequency of 5.11GHz and two resonance frequency which are 6.1GHz and 6.87GHz, which is commonly used in IoT networks, such as Wi-Fi. The antenna is designed with an FR-4 substrate, known for its suitable electrical properties and cost-effectiveness in mass production. The results of this study indicate that the folded dipole antenna, designed using CST Studio Suite and an FR-4 substrate, is a viable solution for enhancing IoT network performance. Its design simplicity, combined with robust performance characteristics, makes it an ideal choice for widespread deployment in the growing IoT landscape.